A SURVEY OF LINEAR CONTROL FOR EXPERIMENTAL BALL AND BEAM WITH MIDDLE AXIS - Huynh, Duy-Khoa; Nguyen, Duc-Anh-Quan; Tran, Duc-Hien; Nguyen, Xuan-Huy; Le, Tuan-Kiet; Pham, Gia-Long; Le, Chi-Danh; Bui, Nguyen-Duc-Huy; Dang, Gia-Huy; Nguyen, Minh-Tam (Asosiasi Peneliti Sriwijaya, 2025)
This paper presents an experimental study of linear control algorithms applied to a Ball and Beam system with a central axis. The focus is on evaluating the ball's ability to remain balanced around the central axis and assessing the stability of linear control strategies in real-world applications. The system is controlled using an STM32F4 microcontroller, which manages a DC motor to adjust the beam's angle in response to the ball's position. Through a series of experiments and data analysis, the study explores the effectiveness of linear control in addressing the system's nonlinear dynamics and discusses the practical challenges faced during implementation. The results contribute to a deeper understanding of advanced control techniques and their potential applications in engineering.